Odpowiedzi

2009-11-30T14:15:32+01:00
A)(x+1)*-x*+2
x*+2x+1-x*+2=2x+3
b)(a-2)*+4-a*
a*-4a+4+4-a*=-4a+8
c)(x+4)*+(x-4)*
x*+8x+16+x*-8x+16=2x*+32=2(x*+16)
d)(2a-1)*-(2a+1)*
4a*-4a+1-4a*-4a-1=-8a
2 5 2
Najlepsza Odpowiedź!
2009-11-30T14:18:56+01:00
1.Podane wyrażenia zapisz w najprostszej postaci:
a)(x+1)²-x²+2=x²+2x+1-x²+2=2x+3
b)(a-2)²+4-a²=a²-4a+4+4-a²=-4a+8
c)(x+4)²+(x-4)²=x²+8x+16+x²-8x+16=2x²+32
d)(2a-1)²-(2a+1)²=4a²-4a+1-(4a²+4a+1)=4a²-4a+1-4a²-4a-1=-8a
1 5 1
2009-11-30T14:26:18+01:00
A) (x+1)² - x² + 2
x² + 2x + 1 - x² + 2
2x + 3

b) (a-2)² + 4 - a²
a² - 4a + 4 + 4 - a²
- 4a + 8

c) (x+4)² + (x-4)²
x² + 8x + 16 + x² - 8x + 16
2x² + 32

d) (2a-1)² - (2a+1)²
4a² - 4a + 1 - (4a² + 4a +1)
4a² - 4a + 1 - 4a² - 4a - 1
- 8a

Mam nadzieję że jest dobrze xD jbc pisz na priv :)